Localized Juvenile Spongiotic Gingival Hyperplasia: A Report of Four Cases and Literature Review. Issue 1 (13th February 2018) - Fernandes, Diego T.; Wright, John M.; Lopes, Silvia Maria P.; Santos‐Silva, Alan R.; Vargas, Pablo A.; Lopes, Márcio A.
Abstract : Introduction: The aim of this case report is to present a distinct subtype of gingival inflammatory hyperplasia, providing information to avoid diagnostic mistakes and overtreatment. Also, an unexpected progression of the lesion is shown. Furthermore, a review of the literature to discuss the pathogenesis, diagnosis, treatment, and the need for new therapeutic approaches is presented. Case Series: The authors report four cases of localized juvenile spongiotic gingival hyperplasia involving the anterior maxillary gingiva with distinct clinical features. The patients were followed for a period of 1 to 9 years, and the evolution of the lesions was documented. Surgical excision or therapy by topical steroids was used to treat the lesions. Conclusions: The long‐term follow‐up provides important information for clinicians not to eliminate older patients for lesion diagnosis. Although surgical excision should not be recommended for all cases, considering the risk of esthetic problems, the treatment modality using topical steroids was not permanently effective in the authors' cases. Investigations about new esthetic treatment modalities for lesions are needed.